A new species of Dieucoila (Hymenoptera Figitidae) associated with Drosophila suzukii (Diptera Drosophilidae) in Argentina - Reche, Vanina Anadina; Gallardo, Fabiana Edith; Funes, Claudia Fernanda; Escobar, Lorena Ines; Ovruski Alderete, Sergio Marcelo; Kirschbaum, Daniel Santiago (Department of Agricultural and Food Sciences, Università di Bologna, 2021)
Drosophila suzukii (Matsumura) (Diptera Drosophilidae), spotted-wing Drosophila (SWD), has recently invaded Argentina, spreading very quickly through different fruit-growing regions. Because of the risk represented by SWD for the national berry industry, it is necessary to develop biological alternatives for its control. Determine the presence of native natural enemies associated with SWD is important to develop biological control programs against this pest. In this study, we present the results of a field survey aimed to collect and identify Hymenoptera parasitoids associated with SWD in organic raspberry crops. We found an almost irrelevant parasitization rate on SWD pupae. The few parasitoids collected were identified as a new species of Dieucoila Ashmead, Dieucoila octoflagella Reche sp. n., which is here described and characterized in comparison with other species in the genus Dieucoila.